Connecting biogeography, ecology, and history through a game-based learning approach - Almeida, Dayana; Pinheiro, Lincoln Brum Leite Gusmão; Guerrero, João Vitor Roque; Costa, Rômulo Theodoro; Trevisan, Diego Peruchi; Scariot, Eliziane Carla; Brisbois, Jérémy; Moschini, Luiz Eduardo (American Journal of Social Sciences and Humanities, 2024)
Biogeography, the study of the distribution of plants, animals, and other living beings on Earth, is an interdisciplinary science that is naturally based on several distinct disciplines, such as history, ecology, and geology. Nevetheless, to connect all these subjects may be tricky for beginners undergrad students. One useful tool is the Game-Based Learning (GBL) approach, a well-documented strategy for stimulating curiosity and enhancing student engagement in formal education. However, selecting appropriate games for GBL is difficult, especially when aiming for a multidisciplinary courses as ecology or geography, for instance, where educators need to teach natural and social sciences combined. The present work explores the use of an ancient type of unbalanced board game – the hunting games – prevalent across various cultures on different continents, to ignite students’ curiosity and guide their interest across multiple disciplines. We begin with a systematic review of the history of hunting games and their educational applications. Subsequently, we examine the possible origins of these games and use this analysis to propose various applications of a game-based learning strategy that integrates natural and social sciences. This research offers valuable insights for educational policymakers and educators, demonstrating the benefits of GBL and highlighting the potential for incorporating cultural heritage aspects into new formal education projects.